Labourer la terre, tisser la vie. Éclats d’analogies dans les Andes sud-péruviennes - Ingrid Hall (Journal de la Société des Américanistes)
Plough the earth, weave the life. Sparkles of analogies in the South Peruvian Andes. The ethnographic datum analyzed in this paper concerns the cultivation of an irrigated plot in a peasant community of the South Peruvian Andes (Calca, Cusco). We will focus on the analogies made by peasants, which relate to two specific semantic domains: human physiology and weaving techniques. We propose a presentation of each punctual analogy according to the agricultural cycle. Interpretation is not our main proposal as we are more interested in the way analogies are structured between them. We will use the concept of schemata defined by Bourdieu (1980) as « generator of practice » and by Descola (2005) as « integrator ».